Stanchions of the Snps Freight Wagon – Structural Solutions and Mechanical Loading during Log and Sawn Timber Transport (Current Problems in Rail Vehicles, 2025)
The article discusses the stanchion system of platform wagons. It contains an overview of standardized solutions, which is supplemented by specific solutions known from operation. The article does not aim to provide a detailed overview of all solutions. The main emphasis is placed on the design solution and optimization of the stanchion system on the Snps wagon. It ensures the safe transport of logs, including sawn timber without damaging its edges during transport.
Keywords: log and sawn timber transport; stanchions; Snps wagon